2019
DOI: 10.1016/j.bjae.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and management of right ventricular dysfunction

Abstract: Mesh keywords: right ventricle, Right ventricular dysfunction, critical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Although we have identified important associations between possible causative mechanisms and abnormal RVFWLS, it is important to highlight that in general patient characteristics were similar between normal RVFWLS and abnormal RVFWLS groups. RVD is increasingly recognised as manifesting in a covert manner [37]. We have found that RVD can be subtle and difficult to diagnose clinically; however, it has a significant impact on survival.…”
Section: Discussionmentioning
confidence: 97%
“…Although we have identified important associations between possible causative mechanisms and abnormal RVFWLS, it is important to highlight that in general patient characteristics were similar between normal RVFWLS and abnormal RVFWLS groups. RVD is increasingly recognised as manifesting in a covert manner [37]. We have found that RVD can be subtle and difficult to diagnose clinically; however, it has a significant impact on survival.…”
Section: Discussionmentioning
confidence: 97%
“…The results of our study would prompt a serious and organized approach prior to intubation of critically ill patients with pre-existing RV dysfunction. 37 The findings support potential interventions and therapies targeting RV function and hemodynamic parameters' optimization before intubation. This may include pre-intubation hemodynamic support with vasoactive and inotropic medications, 38,39 judicious intravenous fluid bolus, 18,40 cautious use of inductive sedative medications, pre and apneic oxygenation, 1,25,41 awake intubation versus modified rapid sequence or delayed sequence intubation 25,26,42,43 and implementing intubation check list and a bundle protocol for management of complications related to endotracheal intubation in such high risk patients.…”
Section: Discussionmentioning
confidence: 56%
“…Because of this, we have decided to employ the NO in this instance. Nitric oxide improves V/Q mismatch, oxygenation, RV systolic function, and mixed venous oxygen saturation by reducing PVR only in parts of the lung that are well ventilated [9].…”
Section: Discussionmentioning
confidence: 99%